2012
DOI: 10.1007/s00534-012-0531-9
|View full text |Cite
|
Sign up to set email alerts
|

Poor prognosis of KRAS or BRAF mutant colorectal liver metastasis without microsatellite instability

Abstract: In this study, all tumors in the cohort of CRLM patients were non-MSI tumors, suggesting MSI cancer in primary CRC would rarely reveal metastatic potential. KRAS and BRAF mutations are suggested to be poor prognostic factors in CRLM. Genetic information has an essential role as a prognostic marker and could contribute to the decisions on treatment strategy for CRLM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 44 publications
5
49
1
2
Order By: Relevance
“…Interestingly, only 1 patient (1.5 %) had a high MSI tumor, which is consistent with previous data noting that MSI-positive status is only present in 0-3 % of CRLM patients undergoing hepatectomy. 25 Moreover, many pathologic reports did not necessarily report on mucinous histology, Crohn-like lymphoid reaction or lymphocyte infiltration. As such, we could not include these variables in the prognostic model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, only 1 patient (1.5 %) had a high MSI tumor, which is consistent with previous data noting that MSI-positive status is only present in 0-3 % of CRLM patients undergoing hepatectomy. 25 Moreover, many pathologic reports did not necessarily report on mucinous histology, Crohn-like lymphoid reaction or lymphocyte infiltration. As such, we could not include these variables in the prognostic model.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] Similarly, KRAS is more frequently mutated in RS CRC, as well as in lung and liver metastases developing from RS primary tumors. 8,13,19,25 mt-KRAS has been associated with prognosis, as well as being predictive of response to anti-EGFR effectiveness. 26,27 In addition, our group and others have reported that KRAS status was prognostic of RFS and OS among patients undergoing surgery for CRLM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the appearance of KRAS gene mutant DNA is associated with resistance to cetuximab in patients with KRAS wild-type colorectal cancers 44. In patients with colorectal cancer, the frequency of the KRAS and BRAF gene mutations is significantly higher in liver metastasis than in primary tumours,45 and KRAS and BRAF gene mutant status is significantly associated with poor outcomes 46. These findings suggest that genetic analysis for the KRAS and BRAF gene mutation in CTCs can be used as a ‘liquid biopsy’ to monitor resistance to cetuximab and to predict metastatic potential in patients with KRAS wild-type colorectal cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 25% of CRLM resected patients were found to harbor the KRAS mutations at codon 12 and 13 and 2–4% were found to harbor the BRAF V600E mutation [712]. Patients harboring these mutations experienced worse survival after resection, potentially due to driving of drug resistance by such mutations [812]. However, our surgical experience revealed that many patients with wild type KRAS and BRAF also exhibited short-term survival after CRLM resection, despite lacking these unfavorable mutations.…”
Section: Introductionmentioning
confidence: 99%